A PROSPECTIVE COHORT STUDY ON INCIDENCE AND RISK FACTORS FOR LOW BIRTH WEIGHT AMONG INSTITUTIONAL DELIVERIES IN KATHMANDU, NEPAL - KARUNA L, SHAKYA; NAVEEN, SHRESTHA; AMOGHA, SHRESTHA; SHARAD R, ONTA (International Journal of Clinical and Biomedical Research, 2015)
Background: Low birth weight (LBW) in developing countries are mainly due to preterm delivery and intrauterine growth retardation. Among other causes of low birth weight, maternal factors are predominant. Aim: This study aimed to identify how strongly maternal risk factors associated to low birth weight. Method and Materials: The study used cohort prospective design among 700 pregnant women attended in antenatal care outdoor patient in Paropakar Maternity Women’s hospital with 6 months follow up. Results: Among 700 respondents, 23 (3%) were lost in follow up. Out of 677 mothers, 151 (22%) gave birth of LBW. The mean birth weight was 2724gm. The mean maternal weight was 48kg, height was150cm and BMI was 21.2kg/m2. The cumulative incidence of LBW in the cohort was 22%. Mothers with weight <45kg had 11 times higher risk of giving of LBW babies (RR=10.92, CI:7.90-15.08); BMI <18.5kg/m2 had 3 times higher risk of giving LBW babies (RR=3.08, CI: 2.30 - 4.12). Mothers without having past history of LBW, and preterm delivery were 0.3 times, and 0.44 times chances of giving LBW babies respectively. There are positive association of LBW with primigravida (RR=1.09), and primiparity (RR=1.41), however, it could not reach statistically significant. Conclusion: The study concluded that maternal weight <45kg is the strongest risk factor for LBW. Other maternal risk factors were weight <45kg, BMI<18.5kg/m2, mothers without past history of LBW, and preterm are also statistically significant to LBW. KEYWORDS: Low birth weight; Cohort; Hospital-based; Maternal anthropometry.